DDB2 represses epithelial-to-mesenchymal transition and sensitizes pancreatic ductal adenocarcinoma cells to chemotherapy - Dardare, Julie; Witz, Andréa; Betz, Margaux; Francois, Aurélie; Meras, Morgane; Lamy, Laureline; Lambert, Aurélien; Grandemange, Stéphanie; Husson, Marie; Rouyer, Marie; Demange, Jessica; Merlin, Jean-Louis; et al. (Frontiers in Oncology, 2022)
Introduction Damage specific DNA binding protein 2 (DDB2) is an UV-indiced DNA damage recognition factor and regulator of cancer development and progression. DDB2 has dual roles in several cancers, either as an oncogene or as a tumor suppressor gene, depending on cancer localization. Here, we investigated the unresolved role of DDB2 in pancreatic ductal adenocarcinoma (PDAC). Methods The expression level of DDB2 in pancreatic cancer tissues and its correlation with patient survival were evaluated using publicly available data. Two PDAC cell models with CRISPR-modified DDB2 expression were developed: DDB2 was repressed in DDB2-high T3M4 cells (T3M4 DDB2-low) while DDB2 was overexpressed in DDB2-low Capan-2 cells (Capan-2 DDB2-high). Immunofluorescence and qPCR assays were used to investigate epithelial-to-mesenchymal transition (EMT) in these models. Migration and invasion properties of the cells were also determined using wound healing and transwell assays. Sensitivity to 5-fluorouracil (5-FU), oxaliplatin, irinotecan and gemcitabine were finally investigated by crystal violet assays. Results DDB2 expression level was reduced in PDAC tissues compared to normal ones and DDB2-low levels were correlated to shorter disease-free survival in PDAC patients. DDB2 overexpression increased expression of E-cadherin epithelial marker, and decreased levels of N-cadherin mesenchymal marker. Conversely, we observed opposite effects in DDB2 repression and enhanced transcription of SNAIL, ZEB1, and TWIST EMT transcription factors (EMT-TFs). Study of migration and invasion revealed that these properties were negatively correlated with DDB2 expression in both cell models. DDB2 overexpression sensitized cells to 5-fluorouracil, oxaliplatin and gemcitabine. Conclusion Our study highlights the potential tumor suppressive effects of DDB2 on PDAC progression. DDB2 could thus represent a promising therapeutic target or biomarker for defining prognosis and predicting chemotherapy response in patients with PDAC.